Exploring the Characteristics of Gender Digital Divide among Secondary School Teachers in Bangladesh (Bangladesh Journal of Public Administration, 2022)
The study contend that with the rapid diffusion of information and communication technologies (ICTs), female teachers’ unequal access to the new information technologies should deserve additional attention to the ‘second order digital divide’- differences in skills and use of ICTs which was dominantly focused on ‘first order digital divide’ by which we refer just to ‘have’ and ‘have-nots’ of digital resources like internet, computer.  Information on characteristics of digital divide i.e. three successive stages of access (material, skill and use) were collected using a semi structured questionnaire along with qualitative method of in-depth interviews and key informant interviews. Survey data were presented by frequency table and Interviews were analyzed with a thematic analysis technique using Van Dijk model. This article explores how the divide comes and which one is the dominant factor reflecting digital divide based on gender. I argue that though female teachers are increasingly internet users, they continue to experience device divide and significant gaps in skills, usage, and online social network access as well. This study argues that government should focuses closer on second order digital divide and female teachers’ self inspiration required too.